Following the Masters: Portrait Viewing and Appreciation is Guided by Selective Detail. (June 2013) - DiPaola, Steve; Riebe, Caitlin; Enns, James T
A painted portrait differs from a photo in that selected regions are often rendered in much sharper detail than other regions. Artists believe these choices guide viewer gaze and influence their appreciation of the portrait, but these claims are difficult to test because increased portrait detail is typically associated with greater meaning, stronger lighting, and a more central location in the composition. In three experiments we monitored viewer gaze and recorded viewer preferences for portraits rendered with a parameterised non-photorealistic technique to mimic the style of Rembrandt (DiPaola, 2009 International Journal of Art and Technology 2 82–93). Results showed that viewer gaze was attracted to and held longer by regions of relatively finer detail (experiment 1), and also by textural highlighting (experiment 2), and that artistic appreciation increased when portraits strongly biased gaze (experiment 3). These findings have implications for understanding both human vision science and visual art.